An Up-to-Date Review of Low-Voltage Ride-Through Techniques for Doubly-Fed Induction Generator-Based Wind Turbines - Benbouzid, M.; Muyeen, S.M.; Khoucha, F. (2015)
This paper deals with low-voltage ride-through capability of wind turbines driven by a doubly-fed induction generator. This is one of the biggest challenges facing massive deployment of wind farms. With increasing penetration of wind turbines in the grid, grid connection codes in most countries require that they should remain connected to maintain reliability during and after a short-term fault. This results in low-voltage ride-through with only 15% remaining voltage at the point of common coupling, possibly even less. In addition, it is required for wind turbines to contribute to system stability during and after fault clearance. To fulfill the low-voltage ride-through requirement for doubly-fed induction generator-based wind turbines, there are two problems to be addressed, namely, rotor inrush current that may exceed the converter limit and the DC-link overvoltage. Further, it is required to limit the doubly-fed induction generator transient response oscillations during the voltage sag to increase the gear lifetime and generator reliability. There is a rich literature addressing countermeasures for LVRT capability enhancement in DFIGs; this paper is therefore intended as an up-to-date review of solutions to the low-voltage ride-through issue. Moreover, attempts are also made to highlight future issues so as to index some emerging solutions.